Developing 3D Animation Materials for EFL Vocabulary Courses - Hidayat, Muhammad Fahreza; Widiastuty, Hesty; Normuliati, Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
Media in Education has an important role in helping to provide students with a better understanding of the learning material being studied. The purpose of this Research and Development project is to develop 3D animated video as a learning material that is both free of copyright violations and tailored meets needs of the students for EFL vocabulary classes. This Research and Development project employ Addie Model with questionnaires, interviews, expert validation, with both large and small group trials form the basis of development. The findings materials have great credentials and the media have good qualifications so that learning media can be used in learning process. This 3d video animation project hoped can help lecturers and teacher in the teaching and learning process and provide comprehensible learning media that for EFL students and a reference material for development in subsequent research.